(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2018)
India is one of the fastest developing countries today. The increased newspaper readership is the result of its growing literacy and access to news on multiple technology and social media platforms. The research is based on overall consumer behaviour towards selection of newspaper with special reference with, India’s leading newspaper brand. Study of consumer behaviour helps the organisations in improvisation of various strategies by understanding customer psyche while evaluating the various alternatives and selecting the best suited one from all available. It also emphasises on factors influencing buying decision and help the firm figure out the consumer’s needs and accordingly provide customised products as desired by them. The current study demonstrates how individuals make decision regarding the preferences towards the selection of a leading newspaper brand. Further, the research provided information which is useful in taking various marketing decision and helped to reduce the risk of consumer shift to various other brands prevailing in the market. The study was conducted through a survey of respondent’s residing in NCR, Delhi. The research concluded that promotional schemes offered by Times of India had a positive correlation with the buying behaviour of the subscribers. However there is a need to strengthen the awareness of the promotional schemes on regular basis and establishing a strong emotional connect with the readers.